Pengaruh Kompetensi, Integritas Dan Independensi Terhadap Kualitas Hasil Audit - Sriyatun; Sugirato, Aris (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to analyze and determine the effect of competence, integrity, and independence on the quality of audit results at the Sumbawa Regency Inspectorate office. The population and sample in this study included all auditors who worked at the Inspectorate of Sumbawa Regency, totaling 35 people. Sampling was carried out using the saturated sampling method or census, so that the entire population was used as a sample. The data analysis technique used is multiple regression analysis to test the relationship between the independent variables (competence, integrity, and independence) and the dependent variable (quality of audit results). Based on the results of hypothesis testing, it was found that partially, competence has a significant effect on the quality of audit results. This shows that the higher the competence of an auditor, the better the quality of the resulting audit results. However, integrity and independence partially do not show a significant effect on the quality of audit results. This finding indicates that the competency factor plays a crucial role in determining audit quality, while integrity and independence in this context have no significant impact. The implications of this research can be taken into consideration for the Sumbawa Regency Inspectorate to increase auditor competence in order to improve the quality of audit results.